The Postmodern, a Conceptual Clarification - Puentes, Juan Camilo (2022)
Because of the profound transformations of the 20th century, especially the technological and communicative ones, political science has adapted new epistemological instruments to explain reality and political phenomena. One of these tools was the postmodern approach, which emerged strongly in the philosophical discipline but, gradually, became an autonomous school of thought that incorporates its own principles, rules, and values. However, either due to the scientific reluctance it generates or its transdisciplinary origin, very little academic literature has rigorously developed the epistemological characteristics of this approach: its normative nature, its conceptual boundaries, or its explanatory scope. For this reason, this article seeks to give an unequivocal meaning to the postmodern in the political universe, accounting for its application as a school of thought (postmodernism) and as a historical period (postmodernity), using a methodology typical of the political theory, specifically, conceptual clarification.